Trade facilitation in times of pandemic: Practices from South and South West Asia - Prabir De (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2020)
The world and regional economies have been hit hard by the COVID-19 crisis. The combined effects of the pandemic and global and national lockdowns have caused havoc in the countries of South and South-West Asia (SSWA), with their trade severely impacted. This paper investigates the subregion's experience implementing trade facilitation measures in the times of COVID-19. The paper indicates that the SSWA countries have achieved remarkable progress in trade facilitation, especially as the COVID-19 crisis progressed. Although the policy responses in the initial months of the outbreak appeared to be fragmented and lacked coherence, countries in SSWA have shown convergence toward simplification of trade procedures, and enhanced transport and logistics and digital trade facilitation. While these measures have helped the SSWA countries secure supply of essential goods and services, some have simultaneously enforced stringent protection measures which represent a risk. The responses to the COVID-19 crisis suggest a greater scope of regional cooperation in the subregion. A cross-border regional protocol may strengthen the preparedness for future pandemics or similar disasters in future. As the current pandemic recedes, there are other opportunities such as in trade finance, cross-border e-commerce, and innovative application of emerging technologies, among others. Digitalizing the trade processes in SSWA, including by signing on to the Framework Agreement on Facilitation of Cross-border Paperless Trade in Asia and the Pacific, would be the next step toward the needed paperless trade environment.
Keywords: F13; F55; I18; 330; Trade Facilitation; ESCAP; COVID-19; Paperless Trade; South Asia; SSWA; Digital Trade; Trade Finance; Customs Procedures